Case Report: Transarterial Chemoembolization in Combination With Tislelizumab Downstages Unresectable Hepatocellular Carcinoma Followed by Radical Salvage Resection - Chao, Jiashuo; Zhu, Qi; Chen, Desheng; An, Xiao; Liu, Aiqun; Zhou, Fei; Yuan, Lin; Wang, Zhaowen; Sun, Hongcheng (Frontiers in Oncology, 2021)
Introduction: Transarterial chemoembolization (TACE) is inefficient at converting unresectable hepatocellular carcinoma (uHCC) to resectable. Treatment with immune checkpoint inhibitors (ICIs) is an emerging strategy for uHCC. Combined therapy of TACE with ICIs is considered to improve the therapeutic effect. Case presentation: A 45-year-old man was diagnosed with a bulky HCC under cirrhotic background without distant metastasis. Curative resection was infeasible, and TACE plus tislelizumab (an ICI targeting PD-1) was applied. The treatment course, starting from TACE and followed by tislelizumab one week later, was repeated every four weeks. After three courses, the tumor showed striking shrink in volume with complete radiological response, which permitted salvage resection. Notably, pathological examination found complete necrosis of the tumor with massive infiltration of lymphocytes in the tumor-nontumor interface and extensive granulomatous inflammation in the surrounding nontumor liver, indicating activated immune response synergistically caused by TACE with tislelizumab. The patient is now living well without tumor recurrence for 6 months after surgery. Conclusion: TACE in combination with tislelizumab may represent a potent strategy for uHCC. Data from randomized clinical trials are needed to assess its safety and effect in the setting of preoperative downstaging therapy.